POLITIC TIMING : ANALISIS POLITIK KEBIJAKAN SOSIAL (BLT DAN BPJS) PEMERINTAHAN ERA SUSILO BAMBANG YUDHOYONO PERIODE 2004-2014 - Christian, Ezra; -, Warsito; Yuwono, Teguh (Journal of Politic and Government Studies, 2018)
ABSTRACT            Social policy is one of the purpose of the national development which aims to create social welfare. Political consideration can not be separated from policy even social policy because the policy establishment and implementation was made by politic actors who have interests in policy so there are many bargains happend in social policy.            BLT and BPJS are quite popular social policies that were issued by the government of Susilo Bambang Yudhoyono which aims to compensate fuel price and ensure public health. Aspects and political meanings are inseparable from those two programs including the political timing. This research was using descriptive qualitative method with in depth interview and document as the data collection.            In the implementation and establishment of BLT and BPJS researcher found one of the political aspect in the policy was the mobilization of voters and the use of BLT and BPJS to face the election in 2009 and 2014 as the political gain of the government of SBY. Researcher also found behavior and responses from SBY in responding the problems and pro contra from BLT and BPJS is to maximize political gain. The researcher also explained the received political impacts of BLT and BPJS in the government of SBY Keywords: Politic, Social Policy, Timing, BPJS, BLT, Mass Mobilization